Gradient of brain mosaic RHEB variants causes a continuum of cortical dysplasia. Issue 2 (12th January 2021) - Lee, Wei Shern; Baldassari, Sara; Chipaux, Mathilde; Adle‐Biassette, Homa; Stephenson, Sarah E. M.; Maixner, Wirginia; Harvey, A. Simon; Lockhart, Paul J.; Baulac, Stéphanie; Leventer, Richard J.
Abstract: Focal cortical dysplasia (FCD) and hemimegalencephaly (HME) are related malformations with shared etiologies. We report three patients with a spectrum of cortical malformations associated with pathogenic brain‐specific somatic Ras homolog enriched in brain ( RHEB) variants. The somatic variant load directly correlated with the size of the malformation, with upregulated mTOR activity confirmed in dysplastic tissues. Laser capture microdissection showed enrichment of RHEB variants in dysmorphic neurons and balloon cells. Our findings support the role of RHEB in a spectrum of cortical malformations confirming that FCD and HME represent a disease continuum, with the extent of dysplastic brain directly correlated with the somatic variant load.